Effects of the COVID-19 pandemic on late postpartum women living with HIV in Kenya - John M. Humphrey; Marsha Alera; Leslie A. Enane; Bett Kipchumba; Suzanne Goodrich; Michael Scanlon; Julia Songok; Beverly Musick; Lameck Diero; Constantin Yiannoutsos; Kara Wools-Kaloustian (Public Library of Science (PLoS), 2023)
Although an estimated 1.4 million women living with HIV (WHIV) are pregnant each year globally, data describing the effects of the COVID-19 pandemic on postpartum women in low- and middle-income countries (LMICs) are limited. To address this gap, we conducted phone surveys among 170 WHIV ≥18 years and 18-24 months postpartum enrolled in HIV care at the Academic Model Providing Access to Healthcare in western Kenya, and assessed the effects of the pandemic across health, social and economic domains. We found that 47% of WHIV experienced income loss and 71% experienced food insecurity during the pandemic. The majority (96%) of women reported having adequate access to antiretroviral treatment and only 3% reported difficulties refilling medications, suggesting that the program's strategies to maintain HIV service delivery during the early phase of the pandemic were effective. However, 21% of WHIV screened positive for depression and 8% for anxiety disorder, indicating the need for interventions to address the mental health needs of this population. Given the scale and duration of the pandemic, HIV programs in LMICs should work with governments and non-governmental organizations to provide targeted support to WHIV at highest risk of food and income insecurity and their associated adverse health outcomes.